2011
DOI: 10.4007/annals.2011.173.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Twisted Alexander polynomials detect fibered 3-manifolds

Abstract: A classical result in knot theory says that for a fibered knot the Alexander polynomial is monic and that the degree equals twice the genus of the knot. This result has been generalized by various authors to twisted Alexander polynomials and fibered 3-manifolds. In this paper we show that the conditions on twisted Alexander polynomials are not only necessary but also sufficient for a 3-manifold to be fibered. By previous work of the authors this result implies that if a manifold of the form S 1 ×N 3 admits a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 46 publications
2
82
0
Order By: Relevance
“…The 'if' direction of the theorem was proved in [5,10,15,31] and the 'only if' direction was proved in [16], extending earlier work in [26,8,9,6,12,13]. This theorem was recently extended to 4-manifolds with a fixed point free S 1 -action by Bowden [7].…”
Section: Remark 4 (1)supporting
confidence: 52%
See 2 more Smart Citations
“…The 'if' direction of the theorem was proved in [5,10,15,31] and the 'only if' direction was proved in [16], extending earlier work in [26,8,9,6,12,13]. This theorem was recently extended to 4-manifolds with a fixed point free S 1 -action by Bowden [7].…”
Section: Remark 4 (1)supporting
confidence: 52%
“…The recent dramatic increase in our understanding of 3-manifolds due to the work of Agol [1,2], Przytycki-Wise [27] and Wise [35,36] now makes it possible to settle Q1 and Q2 for many such 4-manifolds. For example Q1 has been completely answered for 4-manifolds which fiber over a 3-manifold in [12,16] and for those which fiber over a surface in [31,18,33]. To the best of our knowledge, the case of 4-manifolds which fiber over S 1 has not been dealt with in any detail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) In [FV11,FV12b] it is shown that twisted Alexander polynomials corresponding to representations of π 1 (N ) can detect whether R is a fiber or not.…”
Section: Lemma 27 Let (M γ) Be a Taut Sutured Manifold Withmentioning
confidence: 99%
“…A theory of twisted Alexander polynomials was rapidly developed during the past ten years. Among them, one of the most important progress is the determination of fiberedness [FV2] and genus (the Thurston norm) [FV3] of knots by the collection of the twisted Alexander polynomials corresponding to all finite-dimensional representations. For literature on other applications and related topics, we refer to the survey paper by Friedl and Vidussi [FV1].…”
Section: Introductionmentioning
confidence: 99%